On the stability of fissured slopes subject to seismic action - Utili, S.; Abd, A.H. (International journal for numerical and analytical methods in geomechanics, 2016)
Summary A set of analytical solutions achieved by the upper bound theorem of limit analysis and the pseudo‐static approach is presented for the assessment of the stability of homogeneous c, ϕ slopes manifesting vertical cracks and subject to seismic action. Rotational failure mechanisms are considered for slopes with cracks of either known or unknown depth and location. A validation exercise was carried out based on numerical limit analyses and displacement‐based finite‐element analyses with strength reduction technique. Charts providing the stability factor for fissured slopes subject to both horizontal and vertical accelerations for any combination of c, ϕ and slope inclination are provided. The effect of the direction of the vertical acceleration on slope stability is specifically analysed. Yield seismic coefficients are also provided. When the presence of cracks within the slope can be ascertained with reasonable confidence, maps showing the zones within the slope where they have no destabilising effect are provided. Finally, Newmark's method was employed to assess the effect of cracks on earthquake induced displacements. To this end, displacement coefficients are provided in chart form as a function of the slope characteristics. Two examples of slopes subjected to known earthquakes are illustrated. © 2016 The Authors. International Journal for Numerical and Analytical Methods in Geomechanics published by John Wiley & Sons Ltd.